Improving Corporate Governance and Regulatory Compliance Through Business Law : The Role of Advanced Data Analytics in Streamlining Monitoring and Reporting Processes - Adeyinka Lawal; Bisayo Oluwatosin Otokiti; Sibongile Gobile; Adeola Okesiji; Odunayo Oyasiji (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This paper explores the critical role of advanced data analytics in enhancing corporate governance and regulatory compliance through the lens of business law. Corporate governance, which includes principles of accountability, transparency, and responsibility, serves as the backbone of effective business operations. Regulatory compliance ensures that organizations adhere to legal frameworks designed to protect stakeholders and maintain ethical practices. As global regulatory landscapes evolve, organizations face increasing challenges in ensuring compliance with complex, dynamic legal standards. This paper examines how data analytics can streamline monitoring, reporting, and auditing processes, making them more efficient and effective. By leveraging machine learning, artificial intelligence, and predictive analytics, businesses can proactively identify and mitigate compliance risks in real time, enhancing their governance strategies. Case studies demonstrate how organizations have successfully integrated analytics tools to automate compliance reporting and reduce legal risks. This paper also addresses the broader implications of adopting data analytics, emphasizing how it will reshape the future of corporate governance and legal practice. The findings suggest that organizations must invest in cutting-edge analytics technologies and foster a culture of data-driven decision-making to optimize their compliance practices. Ultimately, the integration of data analytics is poised to revolutionize regulatory compliance, ensuring that businesses can more effectively navigate legal complexities and build trust with stakeholders.